Evolution of the Greater Manchester Nutrition and Hydration Programme. (1st August 2020) - Farrer, Kirstine; Rose, Emma; Haynes, Dave; Edwards, Steven; McLaughlin, John
Abstract : Older adults in the community are at risk of malnutrition and dehydration. The present article aims to outline an intervention and a population-health approach to raise awareness of the importance of good nutrition and hydration in later life. This was addressed by developing strong partnership working, governance frameworks and local steering committees. Through the Greater Manchester Nutrition and Hydration Programme, 39 500 older people have been asked about appetite and weight loss and/or used the PaperWeight Armband to date. A total of 5586 people from this population were found to be at risk of malnutrition. All were provided resources, advice and signposting to address this issue. The gross fiscal return on investment over a 5-year period was 3.2-fold and the net present budget impact was £800 000. The long-term cashable fiscal return on investment was estimated at 2.69. This very promising approach has potential to enable older adults to extend their healthy life span and deliver cost savings to the health and care system.